Is Supraclavicular Block as Good as Interscalene Block for Acute Pain Control Following Shoulder Surgery? A Systematic Review and Meta-analysis. (May 2020) - Hussain, Nasir; Costache, Ioana; Kumar, Nicolas; Essandoh, Michael; Weaver, Tristan; Wong, Patrick; Tierney, Sarah; Rose, Peter; McCartney, Colin J. L.; Abdallah, Faraj W.
Abstract : BACKGROUND: Interscalene block (ISB) is the acute pain management technique of choice for shoulder surgery, but its undesirable respiratory side effects have prompted seeking alternatives. Supraclavicular block (SCB) is proposed as an ISB alternative, but evidence of comparative analgesic and respiratory-sparing effects is inconsistent. We compared the analgesic and respiratory effects of SCB and ISB for shoulder surgery. METHODS: Trials comparing ISB to SCB for shoulder surgery were sought. We decided a priori that SCB would be an acceptable alternative if it were noninferior for (1) postoperative 24-hour cumulative oral morphine equivalent consumption (primary outcome, noninferiority margin Δ = −25 mg) and (2) postoperative pain (secondary outcome, noninferiority margin Δ = 4.0 cm·hour –1 ); and superior for (3) postblock respiratory dysfunction (primary outcome). Opioid-related side effects and block-related complications were also evaluated. RESULTS: Fifteen studies (1065 patients) were analyzed. In single-injection blocks, SCB was noninferior to ISB for 24-hour morphine consumption (mean difference for SCB-ISB, MD [95% confidence interval CI] = −3.11 mg [−9.42 to 3.19], Δ = −25 mg); it was also noninferior for 24-hour pain scores (MD = 0.78 cm·hour –1 [0.07–1.49], Δ = 4.0 cm·hour –1 ); and decreased the odds of respiratory dysfunction (odds ratio [OR] [95% CI] = 0.08 [0.01–0.68]). Similarly, in continuous blocks, SCB was noninferior to ISB for 24-hour morphine consumption (MD = 0.46 mg [−6.08 to 5.15], Δ = −25 mg), and decreased the odds of respiratory dysfunction (OR = 0.22 [0.08–0.57]). SCB also decreased odds of minor block-related complications (OR = 0.36 [0.20–0.68] and OR = 0.25 [0.15–0.41] for single-injection and continuous blocks, respectively). Consequently, the null joint-hypothesis was rejected, and SCB can be considered an acceptable alternative to ISB. CONCLUSIONS: For acute pain control following shoulder surgery, high-quality evidence indicates that SCB can be used as an effective ISB alternative. SCB is noninferior for postoperative opioid consumption and acute pain, and it reduces the odds of postblock respiratory dysfunction.